Management of extraretroperitoneal masses in germ cell tumor. Issue 1 (January 2019) - Shah, Ankeet; Nassiri, Nima; Daneshmand, Siamak
Abstract : Purpose of review: Management of extraretroperitoneal (ERP) germ cell tumor (GCT) is a complex clinical scenario faced by urologic oncologists. This article reviews the indications and approach to management of ERP GCT masses. Recent findings: ERP GCT management starts with chemotherapy, and for any residual masses, a careful consideration of surgical intervention versus salvage chemotherapy. Decision-making regarding residual ERP masses hinges on tumor markers, and also the anatomical location. These factors should be contextualized by the patient's risk for teratoma or active GCT, which will impact outcome and thus weigh on decision-making conversations with patients who have advanced disease. Technical challenges of surgical management in the postchemotherapy setting also apply in ERP mass resection. The risks of surgical management in the lung and liver, in particular, add special considerations for morbidity. Surgical resection is often the only recourse for a patient who may have chemoresistant disease and may be an important step in achieving cure. Summary: Surgical management of ERP GCT requires multidisciplinary input, and the urologic oncologist can help guide management with particular emphasis on the indication, timing, and approach to surgical resection.